Sanksi Pidana Pelaku Pencemaran Nama Baik Melalui Media Sosial - Luh Putu Yustika Riani Kusuma; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
Defamation is a continuous and active act in the sense that the suspect and the suspect meet face-to-face and defamation if it is expressed by speaking incorrectly and insinuating about someone to others and the news is heard by the person concerned through issues, or through newspaper media. and electronic media. The Government of Indonesia has made and stipulates legal regulations governing Electronic Information and Transactions in a form of legislation, namely Law no. 11 of 2008 concerning Information and Electronic Transactions. The purpose of this research is to analyze the regulation of criminal acts of defamation through social media and to discuss sanctions for perpetrators of defamation through social media. This research uses normative legal research, using a statutory approach and a conceptual approach. The system for regulating criminal acts of defamation through social media is regulated in Articles 310 and 311 of the Criminal Code and Article 27 paragraph (3) Article 28 paragraph (1) and Article 36 of the ITE Law. The sanctions are regulated in Article 45 paragraph (1) of the ITE Law, namely imprisonment a maximum of 6 (six) months and/or a fine of Rp. 1,000,000,000, - (one billion rupiah).